2009
DOI: 10.1007/bf03178335
|View full text |Cite
|
Sign up to set email alerts
|

Production and partial characterization of extracellular peroxidase produced byStreptomyces sp. F6616 isolated in Turkey

Abstract: -Streptomyces sp. F6616 was found to produce higher levels of extracellular peroxidase activity (0.535 U/ mL) without any inducers than other actinobacteria which are previously reported. Maximum specific peroxidase activity (6.21 U/mg of protein) was obtained after 72 h of incubation at 30 °C in a minimal salt medium (pH 8.0) containing (in wt/v) 0.6% yeast extract and 0.8% ball-milled wheat straw corresponding to a C:N ratio of 4.6:1. Characterization of the peroxidase revealed that the optimal temperature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…F2621 and F6616 [16], Streptomyces viridosporus [25], Streptomyces albus [26], Botryosphaeria rhodina [27], Pleurotus ostreatus and Pleurotus sajorcaju [28], and Streptomyces lavendulae [5]. …”
Section: Resultsmentioning
confidence: 99%
“…F2621 and F6616 [16], Streptomyces viridosporus [25], Streptomyces albus [26], Botryosphaeria rhodina [27], Pleurotus ostreatus and Pleurotus sajorcaju [28], and Streptomyces lavendulae [5]. …”
Section: Resultsmentioning
confidence: 99%
“…Several different soil bacteria have been isolated and characterized based on their capacity to metabolize HA, a principal component of HS, and lignin, a suitable surrogate of biopolymer HS in lab experiments. It was reported that biodegradation of HA and lignin by soil Streptomyces strains and a Novosphingobium sp., respectively, is associated with extracellular peroxidase [7,8] and/or laccase activity [9]. However, bacterial degradation of HS in cold environments remained unexplored and was the impetus for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high‐utility potential of peroxidases, large‐scale production is of utmost importance to the bioeconomy, besides, an effective biocatalytic process requires enhanced enzyme activity and production systems. The production of extracellular peroxidases by some bacteria has been reported . However, most of these reports are on actinomycetes, predominantly Streptomyces species.…”
Section: Introductionmentioning
confidence: 99%